Assessment of Contract Terms and Conditions for Lump-sum Contracts - Othman, Omar (AUC Knowledge Fountain, 2021)
A Contract is a tool that defines the obligations of the contracting parties and assigns the risk between them. Contracts are usually drafted to meet the interests of the owner by addressing the legal issues and liabilities. Meanwhile, less emphasis is placed on clearly communicating the contract terms and ensuring that all contracting parties comprehend their risks and obligations. In a country like Egypt, which has faced drastic economic and political changes in the past few years, and yet is experiencing a boom in the construction sector, many developers tend to draft contracts that might be legally complicated or lacks proper risk allocation to protect their interests. With the lack of sufficient contract evaluation tools, contractors might fail to identify the contractual risks involved with the project leading to the rise of several claims and dispute that might cause delays to the project. Lump sum contracts are becoming increasingly utilized in construction projects around the world. This is because Lump sum contracts allocates most of the risks on the contractor’s burden thus, many contractors may not fully comprehend its provisions nor, implement proper contract evaluation techniques. Accordingly, this research analyses the terms and conditions of 18 lump-sum contracts implemented in Egypt with the objective of devising a contract evaluation method that will enable contractors to analyze a contract and compare the results with previous projects. Each of the studied contracts was analyzed against a list of criteria that were derived from the literature including contractual risks and the factors that cause project delays. The findings create a database of the common lump sum terms utilized in Egypt against which other new contracts can be evaluated. Followed by a two-stage evaluation process, commencing with utilizing Radar charts to compute a contract balance index for every category and analyze specific critical contract provisions of different contracts together. The second stage implements a linear programming technique called Data Envelope analysis to evaluate the entire contract terms together and identify the degree of effectiveness from the Contractor’s perspective. The research contributes with a premilitary conceptualization contract evaluation tools. It presents a webtool that computes the Contract Balance index to provide a numerical indication of the related contract terms. In addition, this thesis also computes an efficiency index that can evaluate the entire contract.